2016
DOI: 10.1108/ijopm-06-2014-0252
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientations, sustainable supply chain initiatives, and reverse logistics

Abstract: Purpose – Global outsourcing shifts manufacturing jobs to emerging countries, which provides new opportunities for improving their economic development. The authors develop and test a theoretical model to predict first, how sustainable supply chain initiatives might influence reverse logistics outcomes and second, the impact of eco-reputation and eco-innovation orientation strategies on the deployment of sustainable supply chain initiatives. The paper aims to discuss these issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
2
21

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(200 citation statements)
references
References 82 publications
13
164
2
21
Order By: Relevance
“…Second, although our sample size and response rate is similar to previous studies that surveyed management executives (e.g. Chiou et al, 2011;Green et al, 2012;Hsu et al, 2016;Tachizawa et al, 2015), such size may limit the generalizability of the research findings. Future research should collect data from other countries with larger sample size to confirm the results obtained in our study.…”
Section: Conclusion and Limitationsmentioning
confidence: 88%
“…Second, although our sample size and response rate is similar to previous studies that surveyed management executives (e.g. Chiou et al, 2011;Green et al, 2012;Hsu et al, 2016;Tachizawa et al, 2015), such size may limit the generalizability of the research findings. Future research should collect data from other countries with larger sample size to confirm the results obtained in our study.…”
Section: Conclusion and Limitationsmentioning
confidence: 88%
“…size, shape, materials) have different impacts. (Hsu et al, 2016) indicated that green packaging includes considerations of cost (materials and shipping), performance (adequate protection of the product), convenience (easy to use), compliance (with legal requirements), and environmental impact Liu et al, 2013). González-Benito and González-Benito (2006) and Murphy and Poist (2000) stressed that among the green initiatives, green logistics received the least importance.…”
Section: Green Packagingmentioning
confidence: 99%
“…The critical issues of reverse logistics are investigated through content analysis in the research of (Pokharel and Mutha 2009). Evidences of the benefits gained from reverse logistics in sustainable supply chain are presented comprehensively in (Alblas et al 2014;Hsu et al 2016). This measure the efficiency of economic sustainability.…”
Section: Conceptual Framework To Manage the Supply Chain Of Sustainabmentioning
confidence: 99%